Motor learning and control for practitioners - Coker, Cheryl A. (Routledge, Taylor & Francis Group, 2018)
With an array of critical and engaging pedagogical features, the fourth edition of this book offers the best practical introduction to motor learning available. This reader-friendly text approaches motor learning in accessible and simple terms, and lays a theoretical foundation for assessing performance; providing effective instruction; and designing practice, rehabilitation, and training experiences that promote skill acquisition.